2015
DOI: 10.1038/srep14670
|View full text |Cite
|
Sign up to set email alerts
|

Logical error rate in the Pauli twirling approximation

Abstract: The performance of error correction protocols are necessary for understanding the operation of potential quantum computers, but this requires physical error models that can be simulated efficiently with classical computers. The Gottesmann-Knill theorem guarantees a class of such error models. Of these, one of the simplest is the Pauli twirling approximation (PTA), which is obtained by twirling an arbitrary completely positive error channel over the Pauli basis, resulting in a Pauli channel. In this work, we te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Small incoherent errors can be well approximated by Pauli errors. In turn, these Pauli error models can accurately reproduce the behavior of quantum error-correcting (QEC) protocols in the presence of incoherent channels [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Small incoherent errors can be well approximated by Pauli errors. In turn, these Pauli error models can accurately reproduce the behavior of quantum error-correcting (QEC) protocols in the presence of incoherent channels [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis conducted for the approximated channels will not be precise due to the fact that parts of the evolutions of the density matrices will be lost when operating with the twirled channels instead of the original ones. Nevertheless, work in the literature has shown that the estimations obtained using the twirling methods presented in this paper are accurate [56].…”
Section: B Approximating Quantum Channels With Twirlingmentioning
confidence: 80%
“…) impact of applying a Pauli twirl approximation converting a general noise channel to a depolarizing noise channel and enabling scalable numerical simulations of Clifford circuits, instead of full-density-matrix simulations, has already been studied in the literature (see, e.g., [56]). Results on small codes suggest that Pauli twirling overestimates the logical error rate, thus providing to some extent an upper bound on the logical error rate [57]. It has also been reported that Pauli twirling is a good approximation for incoherent noise models and worse for coherent errors [58].…”
Section: Coherence Of Noise and Pauli Twirlingmentioning
confidence: 95%